Analysis on Cultivation and Construction of Talent Team in Library and Information Science Specialty - Kaijun, Yu; Ruiyi, Gong (scientific research publishing, 2016)
Cultivation and construction of professional talent team in library and information science have important practical significance on promoting the rapid development of professional information intelligence, improving the service level of information intelligence and meeting people’s requirements for information intelligence. The article firstly analyzes problems existed in cultivation of talent team in library and information science specialty, and then puts forward methods to solve problems with pertinence, providing references for cultivation and construction of talent team in library and information science specialty.
Keywords: Library and Information Science; Professional Talent Team; Cultivation; Construction; Problems